2015
DOI: 10.1038/nature16443
|View full text |Cite
|
Sign up to set email alerts
|

Polarized endosome dynamics by spindle asymmetry during asymmetric cell division

Abstract: During asymmetric division, fate determinants at the cell cortex segregate unequally into the two daughter cells. It has recently been shown that Sara (Smad anchor for receptor activation) signalling endosomes in the cytoplasm also segregate asymmetrically during asymmetric division. Biased dispatch of Sara endosomes mediates asymmetric Notch/Delta signalling during the asymmetric division of sensory organ precursors in Drosophila. In flies, this has been generalized to stem cells in the gut and the central ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
127
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(140 citation statements)
references
References 69 publications
8
127
0
1
Order By: Relevance
“…Here we could confirm this observation and report for the first time that it is equally true for endocytosed molecular agents like Alexa Fluor dextran. This is perhaps not so surprising in light of the recent finding that asymmetric inheritance of vesicles is a naturally occurring cellular process 37 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Here we could confirm this observation and report for the first time that it is equally true for endocytosed molecular agents like Alexa Fluor dextran. This is perhaps not so surprising in light of the recent finding that asymmetric inheritance of vesicles is a naturally occurring cellular process 37 .…”
Section: Discussionmentioning
confidence: 92%
“…In addition, it has been reported that nanomaterials trapped in endolysosomal vesicles are not distributed equally over daughter cells upon cell division 30,34,35 . While this process has been proposed to be a protective mechanism where the daughter cell with the highest NP load can be sacrificed in favour of the daughter cell with the lowest NP content 29,36 , recent findings show that asymmetric inheritance of vesicles is an inherent cell-biological phenomenon 37 . For quantitative cell tracking applications asymmetric inheritance of contrast agents over daughter cells is disadvantageous as it hinders accurate quantification of cell numbers over time, apart from the fact that the brightest signals are coming from cells that are suffering from the highest cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…pIIa because of the asymmetric polymerization/de-polymerization of microtubules (Derivery et al, 2015).…”
Section: Trafficking Mechanisms That Bias and Regulate Notch Activationmentioning
confidence: 99%
“…Asymmetric segregation of Sara endosomes plays an important role in the asymmetric divisions of sensory organ precursors and intestinal stem cells in Drosophila as well as the neural precursors in the zebrafish spinal cord [1820]. This process requires spindle asymmetry, which is generated by microtubule motors, to distribute Sara endosomes asymmetrically [21]. …”
Section: Intracellular Asymmetries Dictate Unequal Cell Fatesmentioning
confidence: 99%